"Se extraña todo:" Family separation and reunification experiences among unaccompanied adolescent migrants from Central America. Issue 176 (9th April 2021) - Patel, Sita G.; Bouche, Vicky; Martinez, William; Barajas, Karla; Garcia, Alex; Sztainer, Maya; Hawkins, Kathleen
Abstract: There has been a record surge of unaccompanied immigrant minors (UAMs) entering the United States, with 86% of those apprehended at the US‐Mexico border originating from the Central American countries of El Salvador, Guatemala, and Honduras. A majority of immigrant children are separated from either one or both parents at various points during the migration process. Although average separations last 4 or more years, and may be deeply distressing, there is little research on family separations among Central American UAMs. Further, little is known about the developmental impact of separations from extended family networks, or about reunification. To address these empirical gaps, this study used community‐participatory qualitative methods to deeply explore the lived experiences and emotional repercussions of family separation and reunification. The sample included 42 adolescents who had all recently migrated to the Western United States from Central America. Thematic analyses revealed that separation experiences are distressing, multifaceted, and have important developmental implications for Central American UAMs. Results illustrate the socioemotional toll that family separation and reunification can have on this vulnerable population, and highlight the need for culturally responsive, developmentally informed, and contextually appropriate care focused on family reunification in order to foster healthy psychosocial adjustment among UAMs.